International Transport Corridors of Eurasia and the Silk Road Economic Belt - M. A. Asaul; I. G. Malygin; A. E. Mokhov (Евразийская интеграция: экономика, право, политика, 2019)
The paper discusses the interaction of Eurasian Economic Union and the Silk Road Economic Belt within the framework of transport routes and international transport corridors development. Today’s Eurasian international transport corridors are reviewed together with the discussion of rebuild and renovated transport infrastructure, considering corresponding realization issues. The paper gives the perspective of collaboration in the transport section of planned Big Eurasian Partnership, which is virtually realized within the framework of the Shanghai Cooperation Organization.